(untitled) (Journal of Information Technologies in Education (ITE), 2010)
The main problems associated with the introduction of distance education in Ukraine are analyzed in this paper. Considering the experience of distance education it has been concluded that it is necessary to improve the legal framework of the distance education and create the informational and educational collaboration of universities in Ukraine.